Persepsi guru sekolah dasar menyikapi pembelajaran abad 21 melalui kearifan lokal Kalimantan Selatan - Dahlia Dahlia; Yudha Adrian; M. Saufi (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
This study aim to find out the teachers’ perceptions to respond 21st century learning with local wisdom of South Kalimantan. This study implemented qualitative approach, with descriptive method. Technique of this study was purposive sampling. Subject of study were an elementary school teacher. Object of study was SDN Teluk Tiram 2 Banjarmasin. Data collection used interview, observation, and documentation. Data analysis in this study, were data reduction, data presentation, and conclusion. Data was checked by data triangulation. The result of this study showed that the teacher of SDN Teluk Tiram 2 Banjarmasin integrating South Kalimantan local wisdom in lesson plan, lesson processing, and evaluation on 2013 curriculum. Local wisdom was integrated in lesson plan that is formed traditional song tittle and traditional game. The traditional song and game were written on lesson plan/RPP. Then, on lesson processing, the teacher lead the students sing traditional song of South Kalimantan on pre-activities. Traditional game of South Kalimantan were played by the students on Friday. On the other moment, traditional game of South Kalimantan were played by the students on Physical subject. On the evaluation process, the teacher evaluated the students by two technique as a follow are test and non-test. On test technique, the teacher gave the students some tests in form essay, multiple-choice, and short answer. On non-test technique, the teacher gave the students to produce some traditional product of South Kalimantan. In addition, the teacher asked the student to perform or show by singing traditional song of South Kalimantan. The researcher gave some suggestion to other researcher to conduct teachers’ perception to respond 21st century learning with local wisdom of South Kalimantan or other local wisdom on other site.